Pineapple cookies characteristics and sensory hedonic acceptance / Nur Farah Syazana Md Salleh ... [et a.] - Md Salleh, Nur Farah Syazana; Tamby Chik, Chemah; Abdullah, Norhidayah; Baba, Noradzhar (Universiti Teknologi MARA, Cawangan Selangor, 2020)
Abstract Pineapple (Ananas Comosus) which is one of Malaysia's fruit commodities confronted the challenge that causes an environmental problem where it produced many waste. Pineapple processing industry produced pineapple core which is slightly harder in texture. It is one of the major wastes generated with 15% of the fruit thrown away or becoming animal feed. Pineapple belongs to the member of the Bromeliaceae, a family of chiefly epiphytic herbs and small shrubs and it is commonly eaten and valued not only because of its flavour and aroma but also because of its dietary material and antioxidant characteristics, including vitamin C and carotenoid material. This study mainly focuses on producing cookies using pineapple core powder, a waste product resulting from canning process of pineapple. The cookies are being produced using 15%, 20% and 30% of pineapple core powder along with other ingredients. Pineapple core powder characteristics and acceptance on cookies were determined by colour analysis, water activity (aw) and sensory evaluation. Pineapple core powder also has the potential to be used for other products in baking industry due to its high fiber content.